Corrosion of upstream metal plumbing components impact downstream PEX pipe surface deposits and degradation. (December 2019) - Huang, Xiangning; Pieper, Kelsey J.; Cooper, H. Kory; Diaz-Amaya, Susana; Zemlyanov, Dmitry Y.; Whelton, Andrew J.
Abstract: Plastic pipes have been and are being installed downstream of metal drinking water plumbing components. Prior research has suggested that such pipe configurations may induce plastic pipe degradation and even system failure. To explore the impact of upstream metal plumbing components on downstream plastic pipes, field- and bench-scale experiments were conducted. Six month old galvanized iron pipes (GIPs) and downstream crosslinked polyethylene (PEX) pipes were exhumed from a residential home. Calcium, iron, manganese, phosphorous, and zinc were the most abundant elements on both GIPs and PEX pipes. Black and yellow deposits were found on some of the exhumed PEX pipe inner walls, which were mainly copper, iron, and manganese oxides (CuO, Cu(OH)2, Fe2 O3, FeOOH and MnO2 ). Follow-up bench-scale experiments revealed that metal levels in the drinking water did not always predict metal loadings on plastic pipe surfaces. The pH 4 water resulted in a greater amount of metals released into the bulk water, but the pH 7.5 water resulted in a greater amount of metals deposited on the PEX pipe surfaces. Hot water (55 °C) induced a greater amount of organics released and higher metal loadings on PEX pipe surfaces at pH 7.5. ATR-FTIR analysis showed that at 55 °C, PEX pipes connected to copper and brass components had the greatest oxidation functional group peak intensity (COOC, CO, and COC). This study highlights potential downstream plastic pipe degradation and metal deposition, which may cause plumbing problems and failures for building owners, inhabitants, and water utilities. Highlights: PEX pipe degradation in metal-plastic hybrid plumbing networks was examined. CuO, Cu(OH)2, FeOOH, Fe2 O3, and MnO2 were found on exhumed PEX pipe surfaces. Moderate water at 55 °C resulted the greatest metal loading on plastic surfaces. PEX pipes exposed to hot water released more organic carbon than cold water. PEX pipes connected to copper and brass had the greatest plastic surface oxidation.